Yoga-Specific Enhancement of Quality of Life Among Women With Breast Cancer: Systematic Review and Exploratory Meta-Analysis of Randomized Controlled Trials - Daline El-Hashimi; Kevin M. Gorey PhD (SAGE Publishing, 2019)
Physical activities during and after cancer treatment have favorable psychosocial effects. Increasingly, yoga has become a popular approach to improving the quality of life (QoL) of women with breast cancer. However, the extant synthetic evidence on yoga has not used other exercise comparison conditions. This meta-analysis aimed to systematically assess yoga-specific effects relative to any other physical exercise intervention (eg, aerobics) for women with breast cancer. QoL was the primary outcome of interest. Eight randomized controlled trials with 545 participants were included. The sample-weighted synthesis at immediate postintervention revealed marginally statistically and modest practically significant differences suggesting yoga's potentially greater effectiveness: d = 0.14, P = .10. However, at longer term follow-up, no statistically or practically significant between-group difference was observed. This meta-analysis preliminarily demonstrated that yoga is probably as effective as other exercise modalities in improving the QoL of women with breast cancer. Both interventions were associated with clinically significant improvements in QoL. Nearly all of the yoga intervention programs, however, were very poorly resourced. Larger and better controlled trials of well-endowed yoga programs are needed.